Comparison the serologic tests used in the diagnosis of brucellosis; brucellacapt, brucella coombs gel, and brucella coombs tube agglutination tests (Annals of Medical Research, 2021)
Aim: Brucellosis is the most common bacterial zoonosis in the world and in our country. The definitive diagnosis of the disease is the isolation of the agent in culture, but in routine diagnosis serologic tests are mostly used. In the routine serological diagnosis of brucellosis, rose bengal, standard tube agglutination (STA) and coombs tube agglutination (CTA) tests were used. The aim of this study was to determine the effectiveness of Brucellacapt (BCAP) and Coombs Gel (CJ) tests by comparing with STA and CTA tests. Materials and Methods: A total of 100 samples (47 positive and 53 negative by CTA test) were included in the study between June 2018 and July 2019. Titters detected as ≥1 / 160 in STA, CTA, BCAP (METSER Brucella test with Coombs, Savas Medical, Istanbul), CJ (ODAK Brucella Coombs Gel test, Toprak Medical, Istanbul) tests were accepted as positive. Cohen kappa (κ) analysis was used to evaluate the consistency between the tests. Results: Out of 100 samples included in the study were found positive, 20 with STA, 48 with CAP and 53 with CJ tests, respectively. Among the 47 patients who were positive with CTA test, 44 were positive with BCAP and CJ tests, also 2 of them were negative with BCAP and 1 with CJ test. Among the samples found negative with the CTA test, 3 were found positive with BCAP and 7 with the CJ test. STA test was negative in 27 samples that were positive by CTA test. κ = 0.900 for CTA and BCAP, κ = 0.841 for CTA and CJ, κ = 0.860 for BCAP and CJ; showed a high level of agreement. The STA test showed a very low level of agreement with all three methods (κ = 0.440 for CTA with STA, κ = 0.426 for BCAP with STA, κ = 0.363 for CJ with STA). Conclusion: Compared to CTA testing, the applicability of BCAP and CJ tests is easier. Among the three tests, the CJ test gives the fastest results. In the serologic diagnosis of brucellosis, BCAP and CJ test can be used because of high compatibility with CTA test, and it is thought that the compatibility between the tests should be evaluated with more comprehensive studies.
Keywords: Brucellosis; coombs tube agglutination; brucellacapt; coombs gel test; serology; rose bengal